2017
DOI: 10.18632/oncotarget.14609
|View full text |Cite
|
Sign up to set email alerts
|

Bradykinin regulates cell growth and migration in cultured human cardiac c-Kit+ progenitor cells

Abstract: Bradykinin is a well-known endogenous vasoactive peptide. The present study investigated the bradykinin receptor expression in human cardiac c-Kit+ progenitor cells and the potential role of bradykinin in regulating cell cycling progression and mobility. It was found that mRNA and protein of bradykinin type 2 receptors, but not bradykinin type 1 receptors, were abundant in cultured human cardiac c-Kit+ progenitor cells. Bradykinin (1-10 nM) stimulated cell growth and migration in a concentration-dependent mann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 42 publications
1
34
0
Order By: Relevance
“…In our previous study, bradykinin at 10 nmol L −1 remarkably stimulates cell growth and migration 10. We therefore utilize the 10 nmol L −1 bradykinin in this study to investigate whether the stimulation of cell growth and migration is linked to Ca 2+ signalling induced by bradykinin.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In our previous study, bradykinin at 10 nmol L −1 remarkably stimulates cell growth and migration 10. We therefore utilize the 10 nmol L −1 bradykinin in this study to investigate whether the stimulation of cell growth and migration is linked to Ca 2+ signalling induced by bradykinin.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently demonstrated that SOCE channel participates in regulating cell growth and migration,13 and bradykinin promotes cell cycling progression and mobility in cultured human cardiac c‐Kit + progenitor cells 10. To investigate whether the stimulation of cell cycling progression and mobility by bradykinin is related to Ca 2+ signalling.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations